Dekoloniale und postkoloniale Perspektiven in der Friedens- und Konfliktforschung Verortungen in einem ambivalenten Diskursraum - Dittmer, Cordula; Nomos Verlagsgesellschaft (Zeitschrift für Friedens- und Konfliktforschung Sonderband, 2018)
The perspectives of decolonisation and postcolonialism still remain on the margins of peace and conflict studies in Germany. This special issue offers a first overview of how key concepts of peace and conflict studies, such as violence, vulnerability, flight, statehood, space, counterinsurgency policy or the identity of young Colombian adults, could benefit from the aforementioned perspectives. The contributions it contains come from political science, critical geography, refugee studies, disaster and vulnerability research, social psychology and sociology.With contributions byClaudia Brunner, María Cárdenas, Sven Chojnacki, Cordula Dittmer, Christiane Fröhlich, Alke Jenss, Daniel Lorenz, Fabian Namberger, Ruth Streicher, Gerdis Wischnath